Economic Integration, Currency Union, and Sustainable and Inclusive Growth in East Africa - Heshmati, Almas (Advances in African Economic, Social and Political Development, 2016)
This edited volume focuses on economic integration, currency union, and sustainable and inclusive growth in East Africa. It consists of twelve interrelated studies that provide a comprehensive picture of the state and determinants of economic development and cooperation among countries in East Africa, such as Burundi, Ethiopia, Kenya, Rwanda and Tanzania. The contributions are grouped into five parts: economic integration and its effects on trade; common currency and exchange rate; research, innovation, and knowledge, and shadow economics and corruption; inclusive and sustainable growth; and the conflict-growth nexus and reconstruction. This book will appeal to scholars and decision makers looking for the necessary tools and determinants of economic development and cooperation in East Africa.